A Case Control Study on Risk Factors Associated with Low Birth Weight Babies in Eastern Nepal - Ravi Kumar Bhaskar; Krishna Kumar Deo; Uttam Neupane; Subhadra Chaudhary Bhaskar; Birendra Kumar Yadav; Hanoon P. Pokharel; Paras Kumar Pokharel (International Journal of Pediatrics)
Background. This study was done to assess the maternal and sociodemographic factors associated with low birth weight (LBW) babies. Methods. An unmatched case control study was done involving 159 cases (mothers having LBW singleton babies) and 159 controls (mothers having normal birth weight singleton babies). Results. More than 50% of LBW babies were from the mothers with height ≤145 cm while only 9.43% of NBW babies were from the mothers with that height. Finally, after multivariate logistic regression analysis, maternal height, time of first antenatal care (ANC) visit, number of ANC visits, iron supplementation, calcium supplementation, maternal education, any illness during pregnancy, and hypertension were found as the significant predictors of LBW. However, maternal blood group AB, normal maternal Body Mass Index (BMI), mother’s age of 30 or more years, and starting ANC visit earlier were found to be protective for LBW. Conclusion. Study findings suggest that selectively targeted interventions such as delay age at first pregnancy, improving maternal education and nutrition, and iron and calcium supplementation can prevent LBW in Nepal.